2022
DOI: 10.1111/ajo.13598
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the day case total laparoscopic hysterectomy (TLH) protocol

Abstract: Background Traditionally total laparoscopic hysterectomy (TLH) patients are admitted for 1–2 days post‐operatively. Day case TLH has been proven to be feasible and safe in other countries; however, this tertiary Queensland hospital is one of the first Australian institutions to introduce a day case TLH protocol. Aim To pilot the implementation of our day case TLH protocol assessing the feasibility, safety and patient satisfaction of same‐day discharge. Materials and Methods A retrospective audit of the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Laparoscopic total hysterectomy is highly favored by women who wish to undergo total hysterectomy because of its minimal impact on the patient's ovarian function, minimal invasiveness, and rapid postoperative recovery [1]. Previous clinical studies have found that the choice of perioperative anesthesia protocol not only affects the anesthetic effect but also effectively reduces the occurrence of postoperative cognitive dysfunction, and improves the overall quality of life of patients [2]. As a result, improving the anesthetic regimen in laparoscopic complete hysterectomy has become a focus of clinical studies in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic total hysterectomy is highly favored by women who wish to undergo total hysterectomy because of its minimal impact on the patient's ovarian function, minimal invasiveness, and rapid postoperative recovery [1]. Previous clinical studies have found that the choice of perioperative anesthesia protocol not only affects the anesthetic effect but also effectively reduces the occurrence of postoperative cognitive dysfunction, and improves the overall quality of life of patients [2]. As a result, improving the anesthetic regimen in laparoscopic complete hysterectomy has become a focus of clinical studies in recent years.…”
Section: Introductionmentioning
confidence: 99%